Patients with cardiac amyloidosis have a greater neurohormonal activation than those with non-amyloidotic heart failure. (2nd October 2021) - Vergaro, Giuseppe; Aimo, Alberto; Campora, Alessandro; Castiglione, Vincenzo; Prontera, Concetta; Masotti, Silvia; Musetti, Veronica; Chianca, Michela; Valleggi, Alessandro; Spini, Valentina; Emdin, Michele; Passino, Claudio
Abstract: Background: Neurohormonal activation has never been investigated in patients with cardiac amyloidosis (CA). Methods: Forty-seven patients with amyloid light-chain (AL)-CA and 61 with transthyretin (ATTR)-CA were matched to non-amyloidotic heart failure (HF) patients based on age, sex, left ventricular ejection fraction ranges, renal function and HF therapies. N-terminal pro-B-type natriuretic peptide (NT-proBNP), norepinephrine and renin were dosed. The primary and secondary endpoints were 1-year cardiovascular death or HF hospitalisation, and 5-year cardiovascular death, respectively. Results: Patients with AL-CA had a 10-fold higher NT-proBNP than HF patients (6548 ng/L [2059–15, 097] vs. 692 [243–2241], p < 0.001), and slightly higher norepinephrine (595 ng/L [383–869] vs. 416 [250–693], p = 0.047). Patients with ATTR-CA had higher NT-proBNP (3984 ng/L [2275–9505] vs. 1751 [470–4768], p = 0.006), norepinephrine (552 ng/L [344–855] vs. 441 [323–601], p = 0.020), and renin (14 mU/L [8–80] vs. 10 [4–34], p = 0.017). Patients with AL- or ATTR-CA had more often 2 or 3 neurohormones above the corresponding upper reference limits than matched HF patients. NT-proBNP and aldosterone were univariate predictors of the primary endpoint in patients with ATTR-CA, but not in matched controls. NT-proBNP and renin predicted the secondary endpoint in patients with AL-CA, but not in matched controls. Conclusions: Patients with CA display a neurohormonal activation, with some prognostic significance.